A moderate position in the debate on the possibility and moral utility of the ethical standards codification - Andrzej Klimczuk (Annales. Ethics in Economic Life, 2017)
The popularisation of drawing up codes that are addressed to various social groups is one of the features of the modern world. However, researchers of the phenomenon have not yet reached a consensus about the moral validity and utility of this activity. The article thoroughly reviews the Polish literature on the subject with regard to the reasons for taking a moderate stance on the codification of ethical standards. The essay describes the main concepts of ethical codes as well as arguments for their approval and rejection. Attention is drawn to the ways of improving the effectiveness of codes and to the ethical decision-making procedure that reconciles the positions of the supporters and opponents of codification.
Keywords: M14; 330; professional ethics; codification; social responsibility; regulation of behavior; standardization; situationism